Assessment of Parents’ Knowledge of Their Infants’ Pain Experience in the NICU - Ashraf, Asma; Fatima, Syeda Mah; Kauser, Syeda Tasneem; Perveen, Kousar (Biological and Clinical Sciences Research Journal, 2025)
Parental involvement in the assessment and management of neonatal pain in the Neonatal Intensive Care Unit (NICU) is essential for improving infant comfort and outcomes. However, gaps persist in parental knowledge, use of pain assessment tools, and engagement in clinical decision-making. Limited evidence exists from the Pakistani context, where resource constraints may further impact parental participation. Objective: To assess the knowledge and involvement of parents in evaluating their infants’ pain experiences in the NICU of a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted from July 2024 to March 2025 at a tertiary care hospital NICU in Lahore. Using non-probability convenience sampling, 153 parents of neonates aged less than one month were recruited. Data were collected through a structured, validated questionnaire that covered demographic characteristics, parental knowledge of pain assessment, and their involvement in the assessment process. Descriptive statistics, including frequencies and percentages, were analyzed using SPSS version 21. Results: More than half of the infants (52.9%) were aged 0–7 days, with a slight female predominance (52.3%). Preterm births accounted for 32.7% of cases, and 64.7% of infants had a birthweight below 2500 grams. Most deliveries were by cesarean section (60.1%). The leading causes for NICU admission were shortness of breath (34.0%) and jaundice (24.8%). Regarding parental involvement, 56.2% reported that their expertise was considered in pain assessments; however, only 41.8% were informed about pain scales, and 26.8% were asked to use standardized tools. Nearly half (49.0%) could identify the type of pain, but many parents were uncertain about assessing its duration and location. Conclusion: While over half of the parents felt included in their infants’ pain assessment, significant knowledge gaps remain, particularly in understanding and applying standardized pain assessment tools. These findings highlight the need for targeted educational interventions to improve parental engagement in neonatal pain management.